The determination of pasture type alfalfa lines - Altinok S.; Türk M.; Erol T.; Akçelik Somay E. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The objective of this research was to characterize 56 collected alfalfa populations growing with two experiments from clones and from seeds in 2010 and 2011. Collected alfalfa populations were affected significantly in most observed traits over two years period. The populations of Akyurt 1.2.3, Kizilcahamam 1.2., Gudul 1, Kazan 1.2., Cankaya 1, Sincan 2, Çubuk 2, Pursaklar 1, Şereflikochisar 1. 2. 3., Nallıhan 1 had erect growing habit and their annual dry matter yield/plant were very high over the two years. They are going to be evaluated for forage-type alfalfa breeding. Apart, all the other populations are going to be subject to a grazetype alfalfa breeding program in near future, because they showed perfect results when investigate of their pasture characters. The first cut dry matter yield/annual dry matter yield (%) was highest on the population of Kalecik 1 (82%). Some of them also had high forage yields, as Golbası 1.2. and Kizilcahamam 1, as well as forage-type. They were growing horizontal, they spread on the surface and under the soil, some of them had rhizomes and they have so many tillers on their crown.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)